Monetary Policy and Financial Repression in Britain, 1951-59 - Allen, William A.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
British monetary policy was reactivated in 1951 when short-term interest rates were increased for the first time in two decades. The book explores the politics of formulating monetary policy in the 1950s and the techniques of implementing it, and discusses the parallels between the present monetary situation and that of 1951.
Keywords: History, Modern; United Kingdom -- History; Political economy; Macroeconomics; Economic policy; Economic history